Impact of COVID-19 vaccination coverage on global disability burden of Guillain-Barré syndrome - Xīn Gào; Chen Zhao; Junting Yang; Ziming Yang; Jingnan Feng; Siyan Zhan; Dongsheng Fan; Zhike Liu (npj Vaccines)
Abstract The global burden of Guillain-Barré syndrome (GBS), an immune-mediated neuropathy, remains poorly characterized during the COVID-19 pandemic. We analyzed age-standardized years lived with disability (YLD) for GBS from 1990 to 2021 using GBD 2021 data and COVID-19 vaccination coverage from Our World in Data, focusing on 2020–2021. During the pandemic, GBS YLD rates rose dramatically, with greater increases seen in low-SDI regions, females and individuals aged 15–29 years. Higher vaccination coverage was inversely associated with GBS disability burden, exhibiting a non-linear protective effect at moderate to high coverage levels. Causal mediation analysis indicated that 44.6% of this association was mediated by reductions in COVID-19 incidence, highlighting both direct and indirect neuroprotective benefits of vaccination programs. These results underscore the importance of sustaining and expanding the vaccine rollout to mitigate the secondary neurological burden associated with emerging infections.